2017
DOI: 10.1159/000477404
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Quality of Life in Patients with Hormone Receptor-Positive Metastatic Breast Cancer: Treatment Options and Considerations

Abstract: The treatment landscape for hormone receptor-positive metastatic breast cancer continues to evolve as the molecular mechanisms of this heterogeneous disease are better understood and targeted treatment strategies are developed. Patients are now living for extended periods of time with this disease as they progress through sequential lines of treatment. With a rapidly expanding therapeutic armamentarium, the prevalence of metastatic breast cancer patients with prolonged survival is expected to increase, as is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Sexual well-being and somatosensory function are most negatively affected. Vulnerability, psychological distress and preoperative cancer distress are significant negative predictors of quality of life and body image post-BPM Chalasani [ 43 ] 2017 Optimizing QOL in patients with hormone receptor-positive metastatic breast cancer Review NA NA No No Patients with HR-positive disease may receive maximum clinical benefit from endocrine therapy while optimizing QOL Garrido-Oyarzun and Castelo-Branco [ 44 ] 2017 Use of hormone therapy for menopausal symptoms and QOL in survivors Review NA NA No No The management of menopausal symptoms and QOL of patients treated for breast cancer remains an important problem without an optimal solution Marta et al [ 45 ] 2017 QOL in patients treated with radiation therapy Systematic review PubMed 353 No No Significant benefit in HRQOL was often reported when a positive primary outcome was reported Zhou et al [ 46 ] 2017 Impact of endocrine monotherapy and in combination with targeted therapy on QOL Systematic review 3 databases and key conferences 11 No No Users of both treatments experienced similar QOL in the first-line and ET-failure setting relative to patients on ET mono. Moreover, these users experienced better QOL outcomes in some domains in the ET-failure setting relative to ET mono users Mileski et al [ 47 ] 2017 QOL considerations during cancer treatment in invasive ductal carcinoma patients Systematic review …”
Section: Resultsmentioning
confidence: 99%
“…Sexual well-being and somatosensory function are most negatively affected. Vulnerability, psychological distress and preoperative cancer distress are significant negative predictors of quality of life and body image post-BPM Chalasani [ 43 ] 2017 Optimizing QOL in patients with hormone receptor-positive metastatic breast cancer Review NA NA No No Patients with HR-positive disease may receive maximum clinical benefit from endocrine therapy while optimizing QOL Garrido-Oyarzun and Castelo-Branco [ 44 ] 2017 Use of hormone therapy for menopausal symptoms and QOL in survivors Review NA NA No No The management of menopausal symptoms and QOL of patients treated for breast cancer remains an important problem without an optimal solution Marta et al [ 45 ] 2017 QOL in patients treated with radiation therapy Systematic review PubMed 353 No No Significant benefit in HRQOL was often reported when a positive primary outcome was reported Zhou et al [ 46 ] 2017 Impact of endocrine monotherapy and in combination with targeted therapy on QOL Systematic review 3 databases and key conferences 11 No No Users of both treatments experienced similar QOL in the first-line and ET-failure setting relative to patients on ET mono. Moreover, these users experienced better QOL outcomes in some domains in the ET-failure setting relative to ET mono users Mileski et al [ 47 ] 2017 QOL considerations during cancer treatment in invasive ductal carcinoma patients Systematic review …”
Section: Resultsmentioning
confidence: 99%
“…This was similar to the study done by Koo et al .,[ 36 ] who found that breast lump was the most frequent (83%) complaint, followed by nonlump breast symptoms such as nipple abnormalities (7%) and breast pain (6%) and nonbreast symptoms like back pain (1%) and weight loss (0.3%). Chalasani[ 37 ] found that the most common symptoms in the patients of breast cancer were irregularly shaped lump in the breast or armpit, changes in the shape, or size of the breast or nipple, skin dimpling or tethering, or alterations in the appearance of the nipple, or a bloody fluid coming from the nipple and in advance stages bone pain, weight loss may be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer, which is currently most frequently diagnosed in women, requires considerable and timely medical intervention as well as should be treated as a global healthcare priority . Breast cancer can be categorized into three subtypes: estrogen-receptor-positive, human epidermal growth factor receptor (HEF) receptor 2-positive, and triple-negative. , Activation of the estrogen-receptor alpha (ERα) plays a crucial role in cancer cell proliferation because approximately 70% of breast cancer patients highly express ERα. To disrupt ERα signaling, various endocrine therapies have been developed. , Aromatase inhibitors (AIs) reduce estrogen biosynthesis; however, the bone mineral density loss and increasing drug resistance limit their further application. Although selective estrogen-receptor modulators (SERMs) are designed to block estradiol biosynthesis and tumor tumorigenesis signal transduction, the risks of endometrial cancer and drug resistance are also imminent. By contrast, selective estrogen-receptor degraders (SERDs) exhibit favorable ERα degradation and antagonism, which are suitable features to address the drawbacks of AIs and SERMs and have led to significant advances in ERα therapeutics …”
Section: Introductionmentioning
confidence: 99%